Synthetic Intron Improves Transduction Efficiency of Trans-Splicing Adeno-Associated Viral Vectors - LAI, YI (2006)
Trans-splicing adeno-associated viral (AAV) vectors hold great promise in many gene therapy applications. We have shown that rational selection of the gene-splitting site in a therapeutic target gene can lead to extremely efficient trans-splicing vectors [Lai, Y., Yue, Y., Liu, M., Ghosh, A., Engelhardt, J.F., Chamberlain, J.S., and Duan, D. (2005). Nat. Biotechnol. 23, 1435–1439]. Our original strategy requires the screening of endogenous introns that are capable of overcoming the mRNA accumulation barrier. To further develop trans-splicing vectors, we have tested whether the use of a generic synthetic intron can bypass the labor-intensive intron-screening process. Two previously characterized exon/intron/exon junctions (60/60/61 and 63/63/64, respectively) in the 6 kb minidystrophin gene were used as templates to represent highly efficient (60/60/61) and relatively poor (63/63/64) gene-splitting sites. We compared RNA production from the reconstituted viral genome and transduction efficiency of the trans-splicing vectors in dystrophin-null mdx mouse skeletal muscle. Our results suggest that a synthetic intron can successfully overcome the mRNA accumulation barrier at the exon 63/64 junction. Furthermore, when the gene was split at the exon 63/64 junction, the synthetic intron-based vectors performed better than the endogenous intron-based vectors. When the gene was split at the exon 60/61 junction, we observed only nominal improvement in mRNA production. Nevertheless, vectors based on the exon 60/61 junction remain the best set in transduction efficiency. Taken together, our results suggest that optimizing intron sequence may boost the transduction efficiency of trans-splicing AAV vectors. OVERVIEW SUMMARY: Successful transduction of trans-splicing AAV vectors depends on the efficient uptake of both donor and acceptor vectors, unidirectional head-to-tail viral genome recombination, and productive transcription and splicing of the reconstituted genome. In this study, we explored the strategy of using synthetic intron to overcome the transcription/splicing barrier. We hypothesized that substituting a less than optimal endogenous intron with a highly conserved synthetic intron will lead to enhanced mRNA production. On the basis of our previous studies of minidystrophin gene trans-splicing AAV vectors, we replaced endogenous introns with synthetic introns in artificially reconstituted viral genomes and in trans-splicing vectors, respectively. Consistent with our initial hypothesis, we observed significant improvement in mRNA production from constructs based on a poor gene-splitting site, namely, the exon 63/64 junction. Synthetic intron replacement also increased transduction efficiency in vectors based on this junction. However, it never reached the level of our best trans-splicing vectors, namely, those based on the exon 60/61 junction. In summary, we have developed a convenient method of using synthetic intron to overcome the mRNA accumulation barrier in trans-splicing vectors. Additional investigation of factors other than mRNA accumulation will likely help to develop better trans-splicing vectors.